ESTABLISHING ECOLOGICAL COMPENSATION CRITERIA FOR RICE PADDIES IN GUANGXI: PERSPECTIVES FROM LOCAL FARMERS - Torres, Ana (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
Low-carbon rice production technology is vital for safeguarding the ecological health of rice fields. However, the ecological benefits of such practices often fail to motivate rice farmers to adopt these low-carbon methods actively. In response, the Chinese State Council introduced the "Opinions on improving the compensation mechanism for ecological protection" in 2016, emphasizing the principle of "who protects, who benefits; who pollutes, who pays" for equity in ecological compensation. The key to driving rice farmers to protect paddy field ecosystems lies in establishing a fair and reasonable ecological compensation standard. While existing research on ecological compensation has examined subjects, standards, and methods, this study delves into the critical aspect of setting ecological compensation standards. In previous studies, scholars investigated various aspects, including the urban and rural population's perspective on farmland ecological compensation, the carbon measurement method to assess carbon sink function compensation, the calculation of ecological compensation standards for different regions, and diverse compensation methods such as government-based, market-based, tax, and fund-driven compensation.